Effect of Distraction Therapy on Reducing Pain Levels - Winna Kurniasari; Dini Suryani; Sri Mulyati; Richa Tri Septinora (HealthCare Nursing Journal, 2023)
Severe pain during labor causes the mother to experience psychological disorders. Therefore, interventions to reduce labor pain are needed in order to reduce complications for the mother and fetus during the process and after delivery. according to research suggests that 7-54% of mothers give birth without experiencing pain if distraction therapy is done. It turns out that through this distraction or relaxation therapy the smoothness of the birthing process naturally increases. This therapy is also very useful for creating a beautiful birthing experience for mothers giving birth. This study aims to determine the effect of distraction therapy on reducing pain perceived by mothers in the first stage of labor in the BPS Dewi delivery room, Jambi City in 2022. This study was an experimental study with a pre and post design. The research location was conducted at BPS Dewi, Jambi City. The population of this study were all mothers giving birth at BPS Dewi as many as 20 people, and all populations were used as samples. Based on the results of the analysis of the data obtained before the distraction therapy was carried out, the pain scale was obtained with a mean = 4.90 and after the distraction therapy was carried out, the mean = 3.45. So it can be seen that there is a decrease as a result of giving distraction therapy. After recapitulation, there was a mean difference between before and after giving distraction therapy 4.90 to 3.45 with a p value of .000, meaning the effect of distraction therapy on reducing pain levels. It is hoped that this research for health services can improve the quality of services for women giving birth through distraction therapy for mothers who are useful for expediting the delivery process.